Willingness to Pay for Children's Education in Digital era: Bangkok and Vicinity - Kaewbuadee, Saranchana; Kraiwanit, Tanpat (Journal of Humanities and Social Sciences Thonburi University, 2022)
The impact of the COVID-2019 pandemic has acted as a catalyst for the leap in technology, creating a turnaround in all told sectors as a result of the social distancing measures implemented by the Thai government and other countries to prevent the spread of the virus. The education sector has been directly affected by the adaptations of academic institutes. This article aims to use digital media to help children learn and assess the value of their parents’ willingness to pay for education in the digital era through a survey on learning. It can be concluded that learning in the normal style and online are both appropriate, with 83.65% of survey participants being willing to adapt in the future if everything is done online, while 89.42% were in favour of online learning provided it did not place too large a burden on parents, and 66.35% expressed concern that it may cause income loss. The estimated average cost of the internet for children's education in the digital era is 709.66 baht per month, and the average cost of learning equipment is 25,741.08 baht. For the benefit of application, knowledge on the use of digital media should be given to both parents and children. Developing learning and giving advice to children is essential to help build understanding and motivate parent-child interactions. Technology can also be adapted to better suit the lifestyles of people in the city and community more.